Plano de ação para elaboração da carta de serviços da Assembleia Legislativa do Rio Grande do Norte - Vale, Diego (2019)
The present intervention project aims to formulate a plan of action for the elaboration of the Service Charter of the Legislative Assembly of Rio Grande do Norte. This Charter is a tool of communication, an instrument of transparency, a channel of relationship with the citizen and stimulus to social participation, as well as a promotion to the efficiency of the public organization. Its implementation, by the Assembly of Rio Grande do Norte, is scheduled from 2011, by Law 9461, which was not implemented. Specific objectives of the intervention project are to map the public services offered to citizens by the Legislative Assembly of Rio Grande do Norte and their respective sectors, based on resolutions 090 and 091/2017; diagnose how, currently, the services are communicated, requested and executed, with notes of the main difficulties and deficiencies of the sectors; to suggest a checklist model to guide sectors of the Legislative Assembly on the definition of information flows and service provision; and propose a workshop template for the preparation of the Service Letter from the 5W2H planning tool. The steps set forth in the Methodological Guide for the elaboration of the Service Charter and the new Decree 9.094 / 2017 will be considered, which started to treat the transparency tool and the description of the public services by Letter of Services to the User. The kind of research for diagnosis that grounded the proposal is descriptive exploratory. In this sense, semi-structured interviews were conducted with heads of the divisions and nuclei of the Assembly, as well as documentary research, whose data were treated through qualitative analysis.